2017
DOI: 10.1536/ihj.16-571
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronary Stent Fracture on Restenotic Neointimal Tissue Characterization After Drug-Eluting Stent Implantation

Abstract: SummaryAlthough drug-eluting stents (DESs) reduce the rates of in-stent restenosis (ISR) and subsequent target lesion revascularization, stent fracture (SF) after DES implantation has become an important concern because of its potential association with restenosis and stent thrombosis. We aimed to assess the pathogenic impact of SF on in-stent restenotic neointimal tissue components after DES implantation. We analyzed 43 consecutive patients (14 with SF and 29 without SF) with ISR requiring revascularization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, researchers have reported several mechanisms for ISR, such as glucose fluctuation and stent fracture. 13,19) This demonstrates that ISR is still problematic. An improved animal model is required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, researchers have reported several mechanisms for ISR, such as glucose fluctuation and stent fracture. 13,19) This demonstrates that ISR is still problematic. An improved animal model is required.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the interventional method, 13) our improved method requires less laboratory staff and less time. The interventional method requires radiography, which harms the staff and the rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stent fracture, including stent recoil after stent implantation, sometimes causes target lesion revascularization. 1,2) Although the exact mechanism is unknown, the change in angulation of the lesion after stenting, total stent length, vessel tortuosity, the stent design, and overlapping stent are associated with the stent deformation. 3,4) A previous study demonstrated acute recoil was observed in 8.2% of 77 consecutive patients, while late recoil was not observed after WS implantation in the patients' native coronary arteries.…”
Section: Discussionmentioning
confidence: 99%